Efektivitas Ekstrak Black Garlic dalam Menghambat Pertumbuhan Candida albicans - Ratih Iswari Ningtias; Dyah Indartin Setyowati; Ari Tri Wanodyo Handayani (Pustaka Kesehatan, 2020)
Black garlic has many properties naturally can be used as an antifungi. This study aims to determine the effectiveness of Black garlic extract in inhibiting the growth of Candida albicans and knowing the Minimum Inhibitory Concentration (MIC) and Minimum Fungicidal Concentration (MFC) of Black garlic extract against Candida albicans. This study used 5 groups of Black garlic extract concentration, namely 75%, 50%, 25%, 12.5%, and positive controls, with 5 replications. Extraction was carried out using maceration method with 96% ethanol solvent, while the antifungal test was carried out by liquid dilution method. MIC was determined by observing the turbidity and clarity of each test solution and compared to the control solution. MFC was determined by observing the presence or absence of fungi colonies growing on Sabouraud Dextrosa Agar (SDA) media after incubation for 24 hours. The results of the study carried out the Kruskall-Wallis test showed a significance value (p <0.05) which means that there were significant differences in all groups. In the Mann-Whitney test showed a significance value (p <0.05) which means there are differences between treatment groups. The conclusion is that Black garlic extract has the ability to antifungal with MIC at a concentration of 50% and MFC at a concentration of 75%.